The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1017/s146342361900032x
|View full text |Cite
|
Sign up to set email alerts
|

Care-seeking pathways, care challenges, and coping experiences of rural women living with rheumatoid arthritis in Odisha, India

Abstract: Aim: The aim of the study was to explore the care-seeking pathway of rural women living with rheumatoid arthritis (RA) and attending a tertiary health-care facility in Odisha, India. Background: RA is the third leading chronic health condition and causes severe pain and immense psychosocial stress. The prevalence of RA is three to four times higher in women than in men. Furthermore, in India, women delay care seeking due to the prevailing sociocultural norms. Women report more severe sym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(32 citation statements)
references
References 19 publications
(26 reference statements)
4
27
1
Order By: Relevance
“…The true magnitude could even be greater given the lower healthcare-seeking by females in India. [ 27 28 ] Few studies, similar to our results, have demonstrated increased risk of multimorbidity among females. Further, some of these child-bearing age group women may become pregnant.…”
Section: Discussionsupporting
confidence: 88%
“…The true magnitude could even be greater given the lower healthcare-seeking by females in India. [ 27 28 ] Few studies, similar to our results, have demonstrated increased risk of multimorbidity among females. Further, some of these child-bearing age group women may become pregnant.…”
Section: Discussionsupporting
confidence: 88%
“…The most common age group for rheumatoid arthritis in Indian women is between the ages of 35 and 45 years, 19 while the median age at first pregnancy among married women in India is 21 years. 20 Thus, RA occurs in a later age group, which might be one of the probable explanations for the low incidence of clubfoot in babies born to RA mothers.…”
Section: Discussionmentioning
confidence: 99%
“…This study is nested within a larger study on care-seeking behavior for RA (10). A mixed-method explorative study was conducted in a tertiary care medical college and hospital (SCB Medical College) at Cuttack, Odisha, India.…”
Section: Methodsmentioning
confidence: 99%